1992
DOI: 10.1021/j100205a062
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-doped hexarhodium carbonyl clusters on magnesia: structures and promoting effects in ethene hydroformylation

Abstract: Selenium-modified Rh6(CO) 16/Mg0 catalysts were prepared by the reaction of Rh6(CO)16/Mg0 with (CH3)2Se in order to examine the promoting effect of an electronegative additive on Rh catalysis for ethene hydroformylation. The deposited Se (Se/Rh6 = 0.6) enhanced the rate of propanal formation 1.9 times as compared with the case of an undepited catalyst.The selectivity of the hydroformylation was improved from 20 to 50% by the Se addition. To the contrary, the monotonous suppression of ethane formation by increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…From TEM observations, the mean particle size is not altered after Se deposition (around 4 nm), and similar observations have been made for silica-supported catalysts. 329 Whatever the support used, ZrO 2 , 328 SiO 2 , 329 or MgO, 330 the addition of Se promotes the hydroformylation of ethene. On zirconia, the activity enhancement is more pronounced for the GPI-D catalyst than for a coimpregnated one.…”
Section: Miscellaneousmentioning
confidence: 99%
“…From TEM observations, the mean particle size is not altered after Se deposition (around 4 nm), and similar observations have been made for silica-supported catalysts. 329 Whatever the support used, ZrO 2 , 328 SiO 2 , 329 or MgO, 330 the addition of Se promotes the hydroformylation of ethene. On zirconia, the activity enhancement is more pronounced for the GPI-D catalyst than for a coimpregnated one.…”
Section: Miscellaneousmentioning
confidence: 99%
“…It has been known that rhodium is the most active catalyst for hydroformylation. Although the catalyst development for the gas-phase [1,2] and liquid-phase [3][4][5][6] hydroformylation has been performed, the additive effect of various components on heterogeneous Rh catalysts has been investigated [7][8][9][10][11][12][13][14][15]. It has been reported that the additives such as Fe, Zn promote the formation of alcohols in ethylene hydroformylation [1,8].…”
Section: Introductionmentioning
confidence: 98%
“…It has been known that rhodium is most active catalyst for hydroformylation reaction. Although the catalyst development for the gas-phase [1,2] and liquid-phase [3][4][5][6] hydroformylation has been performed, the additive effect of various components on heterogeneous Rh catalysts has been investigated [7][8][9][10][11][12][13]. It has been reported that the additives such as Fe, Zn, and Mo promoted the formation of alcohol in ethylene hydroformylation [7][8][9].…”
Section: Introductionmentioning
confidence: 98%